Arabic translation and validation of the Sinus and Nasal Quality of Life Survey (SN-5) in pediatric patients with chronic rhinosinusitis - Ahmed A. Ragab; Zeinab A. Kasemy; Ahmad M. Hamdan (The Egyptian Journal of Otolaryngology, 2021)
Abstract Background This study aimed to validate the translation of the Sinus and Nasal Quality of Life Survey (SN-5) into Arabic (SN-5a) in pediatric chronic rhinosinusitis (CRS) patients. A prospective cohort randomized controlled study was conducted on 129 children with CRS and 100 age- and sex-matched healthy children. The questionnaire was translated into the Arabic language with cross-cultural adaptation. Caregivers answered the questionnaire during their first visits and after 1 week; to assess test–retest reliability and after 2 weeks of medical treatment to test the questionnaire’s ability to detect changes in patients’ symptoms. The responses of the patients and control groups were compared to assess the external validity. Results The SN-5a showed internal consistency and reliability, with Cronbach’s alpha value being 0.69. Item–item and item–total correlation analysis showed adequate construct validity with a highly significant negative correlation between the SN-5 questionnaire items and visual analog scale (VAS) (p < 0.001). There were highly significant positive correlations between items of the questionnaire in the 1st and 2nd visits at 1 week (p < 0.001). A highly significant difference between the case and control groups had been shown for all SN-5a items (p < 0.001). Two weeks after treatment, there were large changes in all the questionnaire items between the first and last visits (effect size > 0.8 for all). Conclusion The translated SN-5a exhibited adequate construct validity, internal consistency, test–retest reliability, and external validity with quite enough ability to assess the longitudinal changes of the disease.